2017
DOI: 10.1111/ejh.12882
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of health‐related quality of life in longitudinal studies of myeloma patients

Abstract: Objectives: Multiple myeloma (MM) patients report high symptom burden and reduced health-related quality of life (HRQoL) compared to patients with other haematological malignancies. The aim of this review was to analyse published longitudinal studies including MM patients according to a change in HRQoL scores, which is perceived as beneficial to the patient according to two published guidelines. The background of these findings should be in focus in future studies, and HRQoL measurements should be integrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 64 publications
4
49
0
5
Order By: Relevance
“…Twenty‐three longitudinal HRQoL datasets were identified for data extraction. The PRISMA flow diagram for the study selection and subdivision of publications into five treatment categories are presented in Nielsen et al (). The longitudinal PRO data from MM‐015 studies were divided into two treatment categories: first line treatment without autologous stem cell transplantation and maintenance therapy, respectively, because the HRQoL data from those two treatments could be extracted separately from the studies (Dimopoulos et al , , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐three longitudinal HRQoL datasets were identified for data extraction. The PRISMA flow diagram for the study selection and subdivision of publications into five treatment categories are presented in Nielsen et al (). The longitudinal PRO data from MM‐015 studies were divided into two treatment categories: first line treatment without autologous stem cell transplantation and maintenance therapy, respectively, because the HRQoL data from those two treatments could be extracted separately from the studies (Dimopoulos et al , , ).…”
Section: Resultsmentioning
confidence: 99%
“…An important aspect of the generalisability of PRO data results is that most PRO data deviates from patients included in clinical trials. This is also the case for patients with MM because 22 of the 23 studies in the systematic review are clinical trials (Nielsen et al, 2017). Newly diagnosed patients with MM included in clinical trials are not representative for the general MM population and PRO data from clinical trials might not be generally applicable (Klausen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Patient survey data showed that the disease and treatment burden of NDMM were associated with productivity losses on a personal level post‐ASCT, and highlighted that losses were largely due to patients retiring or not returning to full‐time work. The economic model estimated considerable productivity losses following a diagnosis with MM and subsequent ASCT; however, data indicating maintenance therapy may improve patient HRQoL suggests social benefits beyond the economic benefits revealed in the model …”
Section: Discussionmentioning
confidence: 99%
“…2 Nevertheless, the impact on HRQoL of maintenance treatment for patients with MM is not well understood. 11,12 Ixazomib is an oral proteasome inhibitor currently indicated in combination with lenalidomide and dexamethasone, for the treatment of patients with multiple myeloma who have received at least one prior therapy. The phase 3 placebo-controlled, double-blind TOURMALINE-MM3 study investigated ixazomib as a MT following ASCT in adult patients newly diagnosed with MM.…”
Section: Introductionmentioning
confidence: 99%